The problems of adverse effects of television and film on society - William Faure (Communicare)
In this article the author poses the question of how we come to terms with television In the home and all the effects we suppose It to have. The author suggests that sociological factors play as important a rôle In the whole debate of whether television acts as a mirror or a catalyst. He suggests that censorship is not the answer to the question of the adverse effects of television, but rather that a thinking, discerning au- dience must be created. This can generate an understanding of the media based upon a reasoning perspective, and ultimately lead to the development of an audience with its own moral perspective